A Stability Contingent Model of Interpersonal Trust in a Local Government Context - Hirst, Tracey Michelle (Curtin University, 2018)
A tentative Stability Contingent Model of Trust is presented as a result of exploratory, qualitative research into an unexplored area of interpersonal trust in a Local Government context. Findings supported the literature that benevolence and competence are central to trust assessments. An original contribution found stability and locus of causality were also salient. Unusually, both white-collar and blue-collar employees were included and contrasted. Issues for a future research agenda are presented.